Pemanfaatan Situs Benteng ASAKOTA Sebagai Destinasi Wisata di Kabupaten Bima - Hidayati, Sri Wahyu; Subari, Subari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The resistance of the people of Bima in defending the kingdom's territory from Dutch colonial occupation has taken quite a long time where Fort Asakota has an important role as a maritime defense strategy. The purpose of this study was to find out the struggle of the Bima people against the VOC (Verenigde Oost Indische) government from the territory of the Bima kingdom. The results showed that Fort Asakota had an important role in the containment strategy, because it was located in a strategic place to drive away VOC warships that wanted to enter the Bima kingdom because it was in the middle of the sea when high tide and low tide would merge with mainland. Asakota Fort was built during the time of Sultan Abdul Khair Sirajuddin as a sea defense fortress at the entrance to the Bima kingdom. At that time the kingdom of Gowa-Tallo had been defeated by the Dutch company and ended with the Bongaya agreement.